Regionalizing Resilience to Acute Meteorological Events: Comparison of Regions in the U.S. - Summers, Kevin; Harwell, Linda; Smith, Lisa M.; Buck, Kyle D. (Frontiers in Environmental Science, 2018)
Using a Climate Resilience Screening Index (CRSI) that was developed to represent resilience to acute weather events at multiple scales for the United States, nine regions of the United States are compared for resilience for these types of natural hazards. The comparison examines the domains, indicators, and metrics of CRSI addressing environmental, economic, and societal aspects of resilience to acute climate events at county scales. The index was applied at the county scale and aggregated to represent select regions of the United States. Comparisons showed higher levels of resilience in the Northeast and West, including Alaska, (>4.0) while counties in the South Atlantic and South-Central regions exhibited lower resilience (<2.0) to acute climate events. Northeast, West and Mountain regions of the US are characterized by relatively low levels of risk (<0.26), higher levels of governance (>0.60), and above national median scores for society, built environment and natural environment domains which enhances their resilience scores. South Atlantic and South-Central regions of the US are characterized by higher risk scores (>0.31) accompanied by lower levels of governance (<0.48) and below national median scores for society and built environment domains reducing the region's overall resilience.